Implementation of clean technologies as a strategy to improve environmental sustainability in industrial plants (Innovation & Development in Engineering and Applied Science, 2025)
This essay examines the impact of implementing clean technologies in industrial plants to enhance environmental sustainability. Case studies of companies that have adopted clean technologies, such as renewable energies, efficient waste management, and reduction of pollutant emissions, are analyzed. The results demonstrate that the implementation of clean technologies has shown to reduce greenhouse gas emissions and decrease the consumption of natural resources in the studied industrial plants. Furthermore, optimization of production processes and reduction of operational costs are observed. These findings support the importance of adopting clean technologies in the industrial sector to promote more sustainable production. The successful implementation of clean technologies not only benefits the environment but can also generate economic savings and improve the corporate image of companies.
Keywords: Sustainability; Industrial Plants; Clean Technologies; Sustainable Production